THE RELATIONSHIP BETWEEN DIABETES SELF-MANAGEMENT AND DIABETES DISTRESS IN TYPE 2 DIABETES MELLITUS PATIENTS AT JEMURSARI ISLAMIC HOSPITAL, SURABAYA - Nabilla Annisa Pradita; Difran Nobel Bistara; Faridah Umamah; Erika Martining Wardani; Susanti (Nurse and Holistic Care, 2025)
Background: Diabetes mellitus remains a prevalent global disease and can lead to both physical and psychological complications. One of the most common psychological impacts is diabetes distress, which refers to emotional stress caused by the continuous demands of managing diabetes. Objective: This study aimed to analyze the relationship between diabetes self-management and diabetes distress among patients with type 2 diabetes mellitus at Jemursari Islamic Hospital, Surabaya. Methods: This study used a correlational analytic design with a cross-sectional approach. A total of 174 patients were selected using a purposive sampling technique. The independent variable was diabetes self-management education, and the dependent variable was diabetes distress. Data collection instruments included the Diabetes Self-Management Questionnaire (DSMQ) and the Diabetes Distress Scale (DDS). Data were analyzed using the Spearman Rank correlation test, with a significance level of p < 0.05. Result: The results showed a significant relationship between diabetes self-management and diabetes distress (p = 0.001), indicating that higher levels of self-management education are associated with lower levels of diabetes distress. Conclusion: This study concludes that better diabetes self-management is significantly associated with lower levels of diabetes distress among patients with type 2 diabetes mellitus. Improving patients’ ability to manage their condition through consistent and comprehensive self-management education may help reduce psychological distress and enhance overall quality of life.